1998
DOI: 10.1111/j.1523-1739.1998.96457.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Genetic Diversity across the Range of North American Brown Bears

Abstract: Understanding the factors that influence the rate at which natural populations lose genetic diversity is a central aspect of conservation genetics because of the importance of genetic diversity in maintaining evolutionary potential and individual fitness. Concerns about loss of genetic diversity are particularly relevant to large carnivores, such as brown bears ( Ursus arctos ), that are distributed at low densities and are highly susceptible to human-caused population fragmentation. We used eight highly varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(70 citation statements)
references
References 43 publications
5
65
0
Order By: Relevance
“…For example, the degree of genetic differentiation is considerably higher than the values reported for pairwise comparisons among subpopulations in Scandinavia, where F st ranged between 0.01 and 0.14 and Nei's standard distance ranged between 0.03 and 0.38. The genetic distance between the two Cantabrian subpopulations, which are only 30 km apart, are comparable with the values reported for the most distant areas within the continuous distribution of brown bears in North America, which are several thousands of kilometres apart (Paetkau et al 1998). This result also shows that habitat discontinuities such as roads and farmland play a larger role in genetic substructuring of population than linear distance, which has also been seen in populations of Cross River gorilla (Bergl and Vigilant 2007).…”
Section: Genetic Status Of the Bear Population In The Cantabrian Mounsupporting
confidence: 68%
See 2 more Smart Citations
“…For example, the degree of genetic differentiation is considerably higher than the values reported for pairwise comparisons among subpopulations in Scandinavia, where F st ranged between 0.01 and 0.14 and Nei's standard distance ranged between 0.03 and 0.38. The genetic distance between the two Cantabrian subpopulations, which are only 30 km apart, are comparable with the values reported for the most distant areas within the continuous distribution of brown bears in North America, which are several thousands of kilometres apart (Paetkau et al 1998). This result also shows that habitat discontinuities such as roads and farmland play a larger role in genetic substructuring of population than linear distance, which has also been seen in populations of Cross River gorilla (Bergl and Vigilant 2007).…”
Section: Genetic Status Of the Bear Population In The Cantabrian Mounsupporting
confidence: 68%
“…The genetic diversity of the Cantabrian population is lower than in other bear populations considered to have a good conservation status (Paetkau et al 1998;Waits et al 1998) and is comparable with those found in Yellowstone (H e = 0.55; Paetkau et al 1998) and Deosai National Park (Pakistan) (H e = 0.55; Bellemain et al 2007). Yellowstone and Cantabrian populations have had a very similar history.…”
Section: Genetic Status Of the Bear Population In The Cantabrian Mounsupporting
confidence: 60%
See 1 more Smart Citation
“…It describes the probability that two randomly drawn (unrelated) individuals (p ID ) or siblings (p IDsibs ) exhibit identical multilocus genotypes (Paetkau et al 1998). Standard parameters of genetic variation and diversity were calculated for all loci based on individuals sampled in the forest stand and on the genotypes of the seed wings.…”
Section: Discussionmentioning
confidence: 99%
“…The discriminatory power of the whole set of STR loci was evaluated with GIMLET (v. 1.3.3: Valière 2002) by estimating the probability that two individuals drawn at random from the populations showed identical multilocus genotypes by chance (P ID and P ID sib: for the latter, we assumed sibling relationships) (Peatkau et al 1998;Waits et al 2001). We used (Hochberg 1988).…”
Section: Microsatellite Dnamentioning
confidence: 99%